Imaging Beta-Cell Function in the Pancreas of Non-Human Primates Using a Zinc-Sensitive MRI Contrast Agent - Clavijo Jordan, Veronica; Hines, Catherine D. G.; Gantert, Liza T.; Wang, Shubing; Conarello, Stacey; Preihs, Christian; Chirayil, Sara; Klimas, Michael; Evelhoch, Jeffrey L.; Sherry, A. Dean (Frontiers in Endocrinology, 2021)
Non-invasive beta cell function measurements may provide valuable information for improving diabetes diagnostics and disease management as the integrity and function of pancreatic beta cells have been found to be compromised in Type-1 and Type-2 diabetes. Currently, available diabetes assays either lack functional information or spatial identification of beta cells. In this work, we introduce a method to assess the function of beta cells in the non-human primate pancreas non-invasively with MRI using a Gd-based zinc(II) sensor as a contrast agent, Gd-CP027. Additionally, we highlight the role of zinc(II) ions in the paracrine signaling of the endocrine pancreas via serological measurements of insulin and c-peptide. Non-human primates underwent MRI exams with simultaneous blood sampling during a Graded Glucose Infusion (GGI) with Gd-CP027 or with a non-zinc(II) sensitive contrast agent, gadofosveset. Contrast enhancement of the pancreas resulting from co-release of zinc(II) ion with insulin was observed focally when using the zinc(II)-specific agent, Gd-CP027, whereas little enhancement was detected when using gadofosveset. The contrast enhancement detected by Gd-CP027 increased in parallel with an increased dose of infused glucose. Serological measurements of C-peptide and insulin indicate that Gd-CP027, a high affinity zinc(II) contrast agent, potentiates their secretion only as a function of glucose stimulation. Taken in concert, this assay offers the possibility of detecting beta cell function in vivo non-invasively with MRI and underscores the role of zinc(II) in endocrine glucose metabolism.